Ephuta icema Casal, 1969 and its host Auplopus subaurarius Dreisbach, 1963 (Hymenoptera: Mutillidae, Pompilidae) from Brazil - Cambra, Roberto A.; Buschini, Maria Luisa Tunes; Arias, Diomedes Quintero; Brozoski, Fanciele; Lustosa, Priscila Rudiak (Zootaxa, 2017)
The male and female of Ephuta icema Casal, 1969 are reared from the host Auplopus subaurarius Dreisbach, 1963 (Hymenoptera: Pompilidae) that allow to unit both sexes for this mutillid and describe hitherto unknown male. A review of all the previous host records for the genus Ephuta Say, 1836 is given.